Implementasi Manajemen dan Supervisi SD SMP di Kecamatan Suralaga Lombok Timur: Studi Kasus Penilaian Kinerja - Kurniawan, Wardi; Adisan, Adisan; Mujriati, Annisa; Maharani, Aprilia; Astuti, Dini; Baqy, Inayatil; Damayanti, Isniwana; Jauhari, Muhammad Tantawi; Al-Qoyyim, Thufail Mujaddid; Utari, Wiwin Melia; Idrus, Agil Al (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to describe the implementation of school principal management and supervision, as well as their relationship to teacher performance appraisal at the elementary and junior high school levels in Suralaga District, East Lombok. The study employed a qualitative approach with a case study design involving 14 elementary schools as research subjects. Data were collected through interviews, observations, and documentation reviews, then analyzed thematically and supported by quantitative data from education reports. The findings indicate that the management and supervision practices of school principals have a significant influence on improving the quality of learning, particularly in aspects of literacy, numeracy, student character, and teacher professionalism. Schools with strong management practices demonstrated higher education report achievements, whereas schools with weak supervision tended to remain stagnant in learning quality. The study also found that the main weaknesses lie in learning reflection, innovation, and data-based decision-making. Therefore, principal and teacher performance assessments need to be followed up with coaching programs and needs-based training. It is recommended that school supervisors and the Education Office design sustainable and adaptive interventions by strengthening data-driven leadership capacity and empowering high-performing schools as models of best practice. This study emphasizes the importance of systematic, reflective academic supervision oriented toward equitable educational quality improvement.